A Self-Study on Building Community in the Online Classroom - Derek Lee Anderson; N. Suzanne Standerford; Sandy Imdieke (Networks: An Online Journal for Teacher Research, 2010)
This paper portrays a year-long self-study of three teacher educators who examined their individual and collective practices in relation to teaching online. Because of its emphasis on reflection on practice, we chose a self-study method with the goal of improving our own practices (Hamilton, 1998). During the past year, we shared our course syllabi, assignments, and student work; we wrote and shared journal entries, met semi-monthly as critical friends, and revised and reanalyzed the ways we taught online. Our department’s lack of guidelines or expectations for online courses, challenges from resistant colleagues about the integrity of online courses, and pressure from administration to maintain enrollment prompted us to examine our online teaching more systematically and critically; ultimately, this enabled us to improve our teaching of teachers.